2017
DOI: 10.1002/ece3.2788
|View full text |Cite
|
Sign up to set email alerts
|

Insularity effects on bird immune parameters: A comparison between island and mainland populations in West Africa

Abstract: Oceanic islands share several environmental characteristics that have been shown to drive convergent evolutionary changes in island organisms. One change that is often assumed but has seldom been examined is the evolution of weaker immune systems in island species. The reduction in species richness on islands is expected to lead to a reduced parasite pressure and, given that immune function is costly, island animals should show a reduced immune response. However, alternative hypotheses exist; for example, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 79 publications
(133 reference statements)
0
13
0
Order By: Relevance
“…If the closest relative did not occur in the sampling site on the mainland, we used the congeneric species present (e.g. Estrilda spp; see also Lobato et al , 2017). In addition, Ploceus cucullatus is the closest mainland relative of both the São Tomé endemic P. grandis and the Príncipe endemic P. princeps (Staffan Andersson, Göteborg University, pers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the closest relative did not occur in the sampling site on the mainland, we used the congeneric species present (e.g. Estrilda spp; see also Lobato et al , 2017). In addition, Ploceus cucullatus is the closest mainland relative of both the São Tomé endemic P. grandis and the Príncipe endemic P. princeps (Staffan Andersson, Göteborg University, pers.…”
Section: Methodsmentioning
confidence: 99%
“…Estrilda spp. ; see also Lobato, Doutrelant, Melo, Reis, & Covas, 2017). In addition, Ploceus cucullatus is the closest mainland relative of both the São Tom e F I G U R E 1 Map of the Gulf of Guinea, in central-west Africa, illustrating the seven regions sampled within the five islands and the mainland sampling areas (located in Cameroon and Gabon).…”
Section: Host Species and Data Collectionmentioning
confidence: 98%
“…For instance, numerous studies have shown that island populations of a wide range of plants and animals differ from mainland populations with regard to traits such as body size, reproduction, dispersal ability, woodiness, and aggression (reviewed in Whitakker & Fernández-Palacios 2007). Study of physiological differences between island and mainland populations has been more limited, and has focused primarily on tests for differences in immune function with respect to island size and/or parasite diversity (Beadell, Atkins, Cashion, Jonker, & Fleischer, 2007;Lobato, Doutrelant, Melo, Reis, & Covas, 2017;Matson, 2006;Matson & Beadell, 2010;Tompkins, Mitchell, & Bryant, 2006), levels of hormone corticosterone as an index of stress (Müller et al, 2007;Rödl, Berger, Michael Romero, & Wikelski, 2007), digestion efficiency (Sagonas, Pafilis, & Valakos, 2015), and thermoregulatory strategy (Sagonas, Valakos, & Pafilis, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced immune function has also been hypothesized to be an island syndrome trait, directly linked to reduced parasite pressure on islands (Lobato et al, 2017; Matson and Beadell, 2010; Wikelski et al, 2004). Island parasite communities are i) less diverse (Beadell et al, 2006; Illera et al, 2015; Loiseau et al, 2017; Maria et al, 2009; Pérez-Rodríguez et al, 2013), and ii) could be less virulent due to the expansion of the ecological niche expected by the theory of island biogeography.…”
Section: Introductionmentioning
confidence: 99%